1986
DOI: 10.1007/bf01907457
|View full text |Cite
|
Sign up to set email alerts
|

Repeated short periods of regional myocardial ischemia: effect on local function and high energy phosphate levels

Abstract: The effect of recurrent periods of ischemia on the myocardium was investigated in 15 open-chest dogs. Ischemia was produced by 3 minutes of proximal occlusion of the left anterior descending coronary artery. Each occlusion was followed by reperfusion of 3 minutes duration. Forty occlusions with a total of 120 minutes of ischemia were performed, and regional function (sonomicrometry) as well as high energy phosphates (needle biopsies) were determined at the end of the 5th, 20th, and 40th period of ischemia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 33 publications
(40 reference statements)
4
16
0
1
Order By: Relevance
“…Similar results were obtained by Hoffmeister et al ( 14) in openchest dogs subjected to (18); and in conscious dogs after three episodes of exercise-induced ischemia (17). In one study (19) in conscious dogs subjected to five 5-min LAD occlusions, a cumulative effect was found when the intervening reperfusion period was 5 10 min but not when it was 15 min.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar results were obtained by Hoffmeister et al ( 14) in openchest dogs subjected to (18); and in conscious dogs after three episodes of exercise-induced ischemia (17). In one study (19) in conscious dogs subjected to five 5-min LAD occlusions, a cumulative effect was found when the intervening reperfusion period was 5 10 min but not when it was 15 min.…”
Section: Discussionsupporting
confidence: 88%
“…This issue is important because, if the injury ceases after the first few ischemic episodes, then myocardial stunning would be a self-limiting process; on the other hand, if each subsequent ischemic episode continues to inflict additional injury, then the possibility exists that myocardium subjected to recurrent bouts of ischemia may become chronically stunned. Previous investigations have yielded conflicting results, with some (6-10, [14][15][16][17][18][19][20][21][22] but not all (23)(24)(25) studies reporting a cumulative effect. Even the studies that have observed a cumulative effect, however, have uniformly concluded that the decrement in function resulting from each subsequent occlusion becomes smaller with the number of repetitions and that after the first three to five occlusions, subsequent occlusions have little or no effect on postischemic dysfunction (6)(7)(8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no reduction of infarct size, however, in preconditioned dogs after 3 hours of sustained ischemia, an observation consistent with the study by Murry et al 9 In a number of studies, the relation between repetitive coronary artery occlusions and myocardial high-energy phosphate stores was examined. [6][7][8]24 The observations from several groups are in agreement and indicate that repetitive occlusion followed by intermittent reperfusion are not associated with a cumulative metabolic deficit. There is no further decrement in high-energy phosphate stores beyond that which is observed to occur with the initial brief occlusion, and there is a decrease in the rate of high-energy phosphate utilization or a "sparing" effect with each subsequent brief ischemic episode.…”
Section: Discussionsupporting
confidence: 64%